Ethnobotanical survey and phytogeographical study of plants species from genus Acacia in Bénin - LAGNIKA, LATIFOU (My University, 2019)
The genus Acacia, mainly distributed in the tropical and subtropical regions, has been used in traditional medicines for the treatment of microbial infections, malaria, diarrhea, oedema and inflammation. The present study aims to provide a comprehensive data on the distribution and medicinal use of Acacia species. Ethnobotanical survey and phytogeographical study were undertook using field interviews. Informant consensus factor (ICF), frequency of citation (Fc), fidelity level (FL) and use value (UV) were also assessed. A total of 16 species belonging to genus Acacia were inventoried in Benin. A total of 108 informants were interviewed during ethnobotanical survey. Except Acacia auriculiformis, all inventoried species cited by informants were traditionally used to treat various ailments. This species were mostly used as medicinal treatments (93.75 % of the species) and to produce wood and fibers (6.25 %). Leaves, bark and roots were the most used parts and decoction was the most cited method of preparation. A. macrostachya (UV = 1.94), A. nilotica (UV = 1.21), A. hockii (UV = 1.20) and A. ataxacantha (UV = 1.17) and A. sieberiana (UV = 1.15) were the most used species. A. nilotica (75%), A. dudgeonii (67%) and A. seyal (50%). A. nilotica (FL = 75%) and A. dudgeonii (FL = 67%) were the most species cited by informants to treat Digestive System Disorder whereas A. Hockii (67%), A. Senegal (67%), A. ataxacantha (60%), A. erythrocalyx (50%) and A. gerrardii (50%) were cited for Infectious diseases. The extensive literature survey reveals 16 Acacia species distributed in 10 phytogeographic districts in Bénin. These species where mostly used in traditional medicine to treat infectious diseases and Digestive System Disorder. The results of this study open new research perspectives on Acacia species not yet studied.
Keywords: Acacia; ethnobotany; phytogeography; medicinal plants